2001
DOI: 10.1002/mop.1222
|View full text |Cite
|
Sign up to set email alerts
|

S‐Parameter broadband measurements of microstrip lines and extraction of the substrate intrinsic properties

Abstract: Figure 6Error induced by ignoring the dependence of distinctness on bit rate Figure 7 Measurement error when the linear fitted interference distinctness ␥ is used sig glected. If the OSNR of 0.1 nm resolution is 30 dB, which is the worst circumstance, the total ASE noise power is about y20 dB lower than the signal power because of the approximate 1 nm bandwidth of ASE noise. The typical crosstalk signal power is y30 dB lower than the signal power, so the crosstalk signal can be neglected.As a conclusion, the 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Complex r and r values are obtained from the S-parameter processing method developed in [6]. The processing method requires a rigorous electromagnetic analysis of the microstrip cell (direct problem) in order to take into account the quasi-TEM mode dispersion, together with an optimization procedure (inverse problem).…”
Section: Extraction Methods Of the Microstrip Substrate Electromagnetimentioning
confidence: 99%
See 2 more Smart Citations
“…Complex r and r values are obtained from the S-parameter processing method developed in [6]. The processing method requires a rigorous electromagnetic analysis of the microstrip cell (direct problem) in order to take into account the quasi-TEM mode dispersion, together with an optimization procedure (inverse problem).…”
Section: Extraction Methods Of the Microstrip Substrate Electromagnetimentioning
confidence: 99%
“…Thus, numerous electromagnetic characterization methods for film-shaped materials have been developed [1][2][3][4][5][6]. Among the cells used (coaxial, microstrip device, stripline), the microstrip cell produced on the material to be characterized seems to be most suitable one for the electromagnetic characterization of filmshaped magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of liquids and semi-solids, it is easier to have the sample as a superstrate. There have been many investigations into the use of planar circuits for complex permittivity measurements of liquids (Stuchly, 1998, Raj, 2001, Facer, 2001, Queffelec, 1994, Hinojosa, 2001, Chen, 2004 Figures 5 and 6 show typical planar cells for dielectric permittivity measurements of liquid materials. The liquid to be measured completely covers the planar circuit and is enclosed inside a low loss container which is fixed firmly or epoxied on top of the board.…”
Section: Planar Transmission Line Techniquesmentioning
confidence: 99%
“…Various microstrip line-based retrieval methods with different configurations were reported in the literature for characterization of natural materials [18][19][20][21][22][23], however, to the authors' knowledge, no microstrip line-based method is reported for characterization of artificial magnetic materials which are in general biansotropic and dispersive.…”
Section: Introductionmentioning
confidence: 99%